Coastal Community Perceptions of Waste Management as an Effort to Maintain Marine Sustainability in Tapanuli Tengah Regency, North Sumatera - Harahap, Husnul Yaqin; Mahaji, Toga; Siburian, Juliana Pebrina; Anugerah, Tirta; Adiprayoga, Shofian Nanda (Institut Teknologi Sepuluh Nopember, 2024)
This study aims to determine the perception of coastal communities in Central Tapanuli towards waste management as an effort to maintain marine sustainability and formulate waste utilization activities as an effort to increase the income of coastal communities in Central Tapanuli. The research method used in this study is a mixed research method. This study was conducted in three locations, namely in Lubuk Tukko Baru Village and Muara Nibung Village, Pandan District and in Jago Jago Village, Badiri District with a total of 100 respondents in the study. Based on the results of the study, the results of the perception of